Evaluation of technological knowledge transfer between Silicon Fen firms and University of Cambridge based on patents analysis - Asma Rezaei; Ali Reza Kamali (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Silicon Fen (SF) is a cluster of high-tech firms located around the University of Cambridge (UoC) in the UK. This article, for the first time, investigates the technological bonds between SF firms and UoC based on patent analysis covering the period of 1999-2021. We provide a short history of SF, highlighting its early formation and growth, and the role of spin-off firms on its evolution. We employ joint patents generated by UoC and various business sectors of SF to calculate the values of technological collaboration strength (TCS). It is found that the majority of joint patents (61%) are generated by the Pharma/Biotech sector of SF with the highest value of TCS (16.45 10−3). Moreover, the patent's economic values across various business disciplines in SF are calculated based on the total counts of citations. Our observations suggest that senior university academics making spin-off firms in a business cluster around their university can effectively facilitate university-firm technological collaboration. Furthermore, the relatively strong technological bond between UoC and the Pharma/Biotech sector of SF is confirmed to be influenced by the collaboration of the university with its own spin-off firms rather than large independent firms in SF. The outcomes of this research contribute to the knowledge of the collaboration between a main research university and a cluster of firms located in its geographical proximity.
Keywords: 650; patent analysis; silicon fen; spin-off firms; University of Cambridge; university-industry collaboration